Study of the heat transfer characteristics and waste heat recovery of hot gas with coagulative particles flowing through a moving granular bed filter (MGBF). (5th July 2022) - Chen, Junlin; Zhou, Jingzhi; Li, Xunfeng; Huai, Xiulan
Highlights: The waste heat recovery of a moving granular bed filter (MGBF) was investigated. Increasing superficial velocity can improve the heat storage capacity of granules. Reducing granular velocity can improve the heat storage capacity of granules. Granular velocity and superficial velocity greatly affect the waste heat recovery. Abstract: The moving granular bed filter is a promising technology for handling the challenges of hot gas clean-up and waste heat recovery in various fields. The purpose of this study was to investigate the heat transfer characteristics and waste heat recovery of a moving granular bed filter during hot gas clean-up. The novelty of this study lies in its investigation of the heat transfer performance of coagulative particles. Experiments were carried out to study the influence of the flue gas inlet temperature, granular velocity, and filtration superficial velocity. The results revealed that increasing the superficial velocity and inlet temperature and reducing the granular velocity are beneficial for improving the heat storage capacity of granules in terms of single factor. However, moderate granular velocity and superficial velocity are recommended to achieve a high waste heat recovery efficiency considering multiple factors. In the present study, a granular velocity of 2 cm∙min −1 and a superficial velocity of 0.3 m∙s −1 are optimal. The superficial velocity is the main factor affecting the comprehensive heat transfer coefficient. The results reveal that the melting and solidification processes of the coagulative particles affect the heat transfer. They also reveal that improving the heat transfer performance is necessary for enhancement of waste heat recovery. The focus of the present study is essentially the development of a moving granular bed filter that contains coagulative particles for use in the metallurgy industry. The results are significant for the design and evaluation of a moving granular bed filter in practical applications that can improve energy efficiency.